Brain Responses to Peer Feedback in Social Media Are Modulated by Valence in Late Adolescence - Wikman, Patrik; Moisala, Mona; Ylinen, Artturi; Lindblom, Jallu; Leikas, Sointu; Salmela-Aro, Katariina; Lonka, Kirsti; Güroğlu, Berna; Alho, Kimmo (Frontiers in Behavioral Neuroscience, 2022)
Previous studies have examined the neural correlates of receiving negative feedback from peers during virtual social interaction in young people. However, there is a lack of studies applying platforms adolescents use in daily life. In the present study, 92 late-adolescent participants performed a task that involved receiving positive and negative feedback to their opinions from peers in a Facebook-like platform, while brain activity was measured using functional magnetic resonance imaging (fMRI). Peer feedback was shown to activate clusters in the ventrolateral prefrontal cortex (VLPFC), medial prefrontal cortex (MPFC), superior temporal gyrus and sulcus (STG/STS), and occipital cortex (OC). Negative feedback was related to greater activity in the VLPFC, MPFC, and anterior insula than positive feedback, replicating previous findings on peer feedback and social rejection. Real-life habits of social media use did not correlate with brain responses to negative feedback.